Economical importance of Finnish reindeer industry - Nieminen, Mauri; Kemppainen, Jorma (Rangifer, 1999)
Within 15 years favourable weather conditions, antiparasite medication, supplementary feed, modern technology, calf slaughter and other factors all contributed to a vast increase in reindeer, and hence reindeer meat production, so much so that by the early 1990s the total number of reindeer was approaching 430 000, and reindeer meat production exceeded 4 million kg. Due to excess numbers of reindeer, stocks had to be culled. At the same time problems arose with the processing of reindeer meat. As a result, demand slumped and prices plummeted. In a few years the outlook for reindeer management changed drastically. Since then the profession has been marked by uncertainty and change. The number of reindeer is now below the permitted level. In the 1996/97 season, number of living reindeer in herds totalled over 202 000, slaughtered reindeer 80 000 (Fig. 1) and meat production about 2 million kg. Income from slaughtered animals amounted to FIM 58 million.